2014
DOI: 10.1097/inf.0000000000000136
|View full text |Cite
|
Sign up to set email alerts
|

The Population-Based Health Effect of Hand, Foot and Mouth Disease in Children in Shanghai

Abstract: HFMD and EV71 infections have a significant health effect on Shanghai children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 16 publications
0
12
2
Order By: Relevance
“…50 Indeed, children aged below two years were often found to be at a higher risk of developing severe complications. 51, 52, 53 We did not observe any difference in median age between the three clinical groups in the present study. The association of other factors with poor outcomes will be assessed in another article.…”
Section: Discussioncontrasting
confidence: 65%
“…50 Indeed, children aged below two years were often found to be at a higher risk of developing severe complications. 51, 52, 53 We did not observe any difference in median age between the three clinical groups in the present study. The association of other factors with poor outcomes will be assessed in another article.…”
Section: Discussioncontrasting
confidence: 65%
“…Combined with our previous surveillance data, [22, 23] we reason that the principal strategy of controlling the HFMD outbreak in Shanghai is to prevent the EV71 circulation in children through mass EV71 vaccination. In line with previous studies, we also found that persistent fever >3 days, vomiting, startle, and myoclonus can be used as the warning signs for predicting the severe HFMD cases [8, 24].…”
Section: Discussionmentioning
confidence: 84%
“…10 Compared with local children, migrant children had a 100% higher risk for contracting HFMD, and an 81% higher risk for developing severe disease. 29 Due to the fact that the number of migrant children is enormous in urban area which may trigger an outbreak of HFMD or even the epidemic. This may provide targeted guidance assessing climate change-related human health in urban and rural areas for policymakers and medical institutions to better allocation the limited health resources.…”
Section: Discussionmentioning
confidence: 99%